Adiposity in small for gestational age preterm infants assessed at term equivalent age. Issue 5 (19th May 2009) - Giannì, M L; Roggero, P; Taroni, F; Liotto, N; Piemontese, P; Mosca, F
Abstract : Objective: Infants classified as small for gestational age are considered to have developed under adverse intrauterine conditions that lead to lack of fat mass accretion. The aim of this study was to test the null hypothesis that the fat mass in preterm small for gestational age infants assessed at term equivalent age was not different from that of full-term small for gestational age newborns. Design: Observational study. Setting: Northern Italy. Patients: 67 small for gestational age preterm infants and 132 small for gestational age full-term newborns. Main outcome measures: Growth and body composition, assessed by means of a paediatric air displacement plethysmography system, were measured at term equivalent age in the preterm infants and on the third day of life in the full-term newborns. Results: The mean (SD) gestational age of preterm infants was 30.6 (2.3) weeks and their mean (SD) birth weight was 1140 (237) g. At assessment weight was not different between the preterm and full-term infants, whereas the percentage of total body fat mass was higher in the preterm infants (14.3% (SD 4.7%) vs 5.8% (SD 3.5%), p<0.005). Conclusions: Preterm infants, born small for gestational age, appear to be at risk for increased adiposity, which is a risk factor for the development of the metabolic syndrome.